Digital Storytelling with Scratch as a Pedagogical Tool to Enhance Reading Comprehension - Agnes Widyaningrum; Yulistiyanti; Teguh Kasprabowo; Katharina Rustipa; Endang Yuliani Rahayu (ETERNAL (English Teaching Journal), 2026)
Reading comprehension is a foundational skill underpinning students’ success in language learning, critical thinking, and academic achievement. However, many EFL learners experience difficulties engaging with extended and complex texts when reading instruction lacks creative and multimodal elements. This classroom-based study explores undergraduate English Literature students’ perceptions of using Scratch-based digital storytelling in a reading course at the English Literature Department of the Faculty of Law and Language, Universitas STIKUBANK. Grounded in constructivist learning and multimodal literacy theories, the study examines how the integration of technology, creativity, and narrative production is perceived to support students’ engagement with literary texts. Thirty-five students participated in a six-week digital storytelling project in which they digitally retold literary stories using Scratch. Data were collected through a validated 10-item questionnaire (Cronbach’s α = .94) and open-ended student reflections. The findings indicate that students perceived Scratch as an engaging platform that supported their understanding of story structure, character motivation, and thematic meaning. Students also reported increased collaboration, confidence, and enjoyment during reading activities. While the findings are perception-based, the study suggests that Scratch-based digital storytelling holds pedagogical potential for supporting students’ engagement with literary texts, interpretive processes, and digital literacy in EFL literature classrooms, thereby contributing to Sustainable Development Goal 4 (Quality Education).